Quantificação de subpopulações linfocitárias no sangue periférico de cães sadios adultos - Santana, Lucas A.S. [UNESP]; Morais, Fabiana R.; Santana, André M. [UNESP]; Voorwald, Fabiana A. [UNESP]; Santana, Aureo E. [UNESP] (FapUNIFESP (SciELO), 2017)
Flow cytometry has established itself as a useful tool in veterinary practice, particularly for small animals practice. Such knowledge has made necessary the establishment of physiological values for different lymphocyte subpopulations, indispensable to understanding the dynamics of lymphoid cellularity in various pathological conditions. In this sense, the objective of this study was to determine, through cytometric technique, lymphocyte subsets of CD5+CD4+, CD5+CD8+ and CD21+ in four different breeds of domestic dogs, so to add information about the immunological profile of different breeds. A total of 40 adult dogs were used (2-7 years), being males and females of Beagles (G1, n=10), Golden Retrievers (G2, n=10), English Bulldogs (G3, n=10) and crossbreed dogs (G4, n=10). Blood samples were collected by jugular venipuncture, using vacuum flasks system (K2-EDTA). Hemogram and processing of samples for flow cytometry were performed within a maximum of 24 hours after blood collection. Samples were analyzed using FACSCanto device (Becton Dickinson, San Jose, CA, USA). FACSDiva software (Becton Dickinson, San Jose, CA, USA) was used to identify and quantify the CD5+ CD4+, CD5+CD8+, and CD21+, which provided the histogram and the respective table with the number of cells identified by immunophenotyping. The data obtained for T helper lymphocyte count, T cytotoxic/suppressor lymphocyte count and B lymphocytes were tabulated and submitted to analysis of variance by F test. Tukey test at 5% probability was used to compare means between the different breeds of dogs. The average values for CD5+CD8+ cell count in peripheral blood in G1, G2, G3 and G4 were of 155, 206, 544 and 503 cells/uL, respectively. The average values for CD5+CD4+ cell count in peripheral blood in G1, G2, G3 and G4 were of 746, 642, 855 and 1101 cells/uL, respectively. The average values for CD21 + cell count in peripheral blood for G1, G2, G3 and G4 were of 171, 299, 494 and 403 cells/uL, respectively. Therefore, The average number of cells obtained for the subsets of cytotoxic T lymphocytes was significantly higher (p < 0,05) in the British Bulldogs and crossbreed dogs compared to those found in Beagles and Golden Retrievers. Furthermore, it was observed that the average number of cells obtained for the subsets of B lymphocytes was significantly higher (p < 0,05) in English Bulldogs compared to that of Beagles.
Lymphocyte subsets in peripheral blood of adult healthy dogs
Keywords: Dogs; Flow citometry; Lymphocytes